THE INFLUENCE OF LIQUID ORGANIC FERTILIZER AND SOLID WASTE ( SLUDGE ) ON GROWTH AND PRODUCTION OF TOMATOES (Solanum lycopersicum L.) - Suryawaty ,; Frisai Hafiz (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
The objective of this research was to find out the influence of liquid organic fertilizer and solid waste (sludge) to growth and production tomatoes (SolanumLycopersicum L.). Pure varieties were used in this research. This research carried out by using a group random design (SHELVES) Factorial with two factors that are examined, factors giving Multiguna exclusively with 3 level, namely: Mo = Without treatment, M1 =2 ml/1 liter of water, M2 = 4 ml/1liter water. Factors giving Solid waste ( sludge ) with 3 level, namely: S0 = Without treatment, S1 = 3 kg/assassinations, S2 = 6 kg/plots. This research done by using 3 deuteronomy, the number of plants per plot 6 plants, the number of plant samples per plot 3 plants, the number of plots or 27 assassinations, the distance between plots or 50 cm, distance between deuteronomy 100 cm, long-term plots or 150 cm, wide plots or 1 m, wide plots or 100 cm x 150 cm, distance 40 x 40 cm, the number of plants altogether 216 plants, the number of plant samples 81 plants. The result showed liquid organic fertilizer with the dose 4 ml/liter water affected the plants, the highest 53.78 cm, the number of fruit per plant most is 13.12 fruit. Heavy fruit per plant most severe is 333.89 g Solid waste (sludge) have effected on tomatoes, the highest is 50.78 cm, there is no interaction between the liquid organic fertilizer and solid waste (sludge) to all parameters that are measured.Keywords: tomato, fertilizer multiguna exclusive, solid waste ( sludge )